HUBUNGAN BUDAYA ORGANISASI, KEPEMIMPINAN, KEPUASAN TERHADAP KINERJA KARYAWAN DI RUMAH SAKIT - Nur Afnita; Sarah Handayani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
Hospitals as health services have various professionals with different functions, in the field of general health services, specialists, to sub-specialists whose number of staff is adjusted to the type of class of each hospital. Characteristics, enthusiasm for work and loyalty of resources, are a reflection of the image as a character of a hospital so that it can continue to progress continuously and develop employee skills for the sustainability of the organization's existence, especially health services, so the parties like policy makers need to look for strategies to improve performance on employees. This literature review aims to analyze the influence and relationship of several performance factors on employees who work in hospitals, namely organizational culture, leadership and job satisfaction. This research design is included in the literature review obtained from search engines, namely Google Scholar, Researchgate and Garuda Portal. The inclusion criteria in the article search are the time between 2017 and 2021 and the place is only in the hospital. The result of this study is that there is a positive relationship which indicates a significant influence on the independent variables, namely culture in an organization, leadership, and job satisfaction on the dependent variable, namely the performance of employees at the hospital. So the conclusion from this study is that employee performance is strongly influenced by organizational culture, leadership and job satisfaction.